“Evaluación preliminar de fuentes y niveles de fósforo para el cultivo de maíz en suelos ácidos de la banda de shilcayo – San Martín” - Chappa Santa María, César Enrique (1992)
· ~ 1 phosphorus is a nutrient that relatively stable in soil, for this reason when applied on _dosis which exceed the quantities required by crops (used only between 5 and 30%); residue remaining in the soil can be used in greater or lesser proportion by subsequent crops, which is has depending upon the source as fertilizer , the type of soil, the time elapsed since its implementation, the pH and the sown plant species. This study tries to determine the source and level most suitable match for the cultivation of corn, under conditions of extreme acidity, using as sources of calcium and the Fosbayovar rock, triple superphosphate as well as make an economic study to facilitate its possible recommendation. For the field of work phase was used with four replicates, split-plot design using 6 treatments (4 levels of fertilization and 2 witnesses) standardising the levels of nitrogen in the form of chlorine...